2011
DOI: 10.1155/2011/196021
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in Femoral Head Necrosis of Human Bone Tissue

Abstract: Abstract. Osteonecrosis of the femoral head (ONFH) is the result of an interruption of the local circulation and the injury of vascular supply of bone. Multiple factors have been implicated in the development of the disease. However the mechanism of ischemia and necrosis in non-traumatic ONFH is not clear. The aim of our investigation was to identify genes that are differently expressed in ONFH vs. non-ONFH human bone and to describe the relationships between these genes using multivariate data analysis. Six b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recent evidence suggests that abnormalities in the bone metabolism pathway are implicated in its pathogenesis (Balla et al, 2011;Wen et al, 2012;Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that abnormalities in the bone metabolism pathway are implicated in its pathogenesis (Balla et al, 2011;Wen et al, 2012;Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated well that decreased proliferation capacity, enhanced apoptosis, impaired osteogenesis and enhanced adipogenesis were found in BMSCs of ONFH patients (3,4). In addition, aberrant gene expression was also found in BMScs of ONFH patients and thus, is considered as the major cause of the dysfunction of BMScs, particularly in the imbalance between osteogenesis and adipogenesis (5).…”
Section: Introductionmentioning
confidence: 93%
“…Non-traumatic osteonecrosis of femoral head (ONFH) represents an intractable bone disease, pathophysiologically characterized by progressive collapse of the femoral head because of a disturbance in the supply of blood and anomalies in the fibrinolytic system [1,2]. Since this ischemic necrosis of the femoral head and deterioration of hip joint function may significantly affect patient quality of life, it is urgent to clarify the pathogenic mechanisms regarding this disease.…”
Section: Introductionmentioning
confidence: 99%